PENERAPAN SISTEM MEKANISASI DALAM KEGIATAN PENEBANGAN JATI UNTUK MENGURANGI KETERGANTUNGAN TERBATASNYA PENYEDIAAN TENAGA BLANDONG DI JAWA - Maman Mansyur Idris; Soenarno Soenarno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Sastrodimedjo, (1975) pointed out that the present trend of wood processing industry development and formal education of younger generation caused some problems, especially in the sustainabiliy of forest worker supply in Java.Based on this consideration an alternatif for most widely applied felling system, i.e. manual felling system, needs to be sought. With regard to this problem a study was conducted at three Sub Forest District (RPH), namely Temenggeng, Pasar Sore and Sumberogo in Central Java to compare 3 (three) felling systems in teak forest.The result of the study revealed that the teak felling productivity averages on 2 years gilrded teak with mechanical, manual and combination systems applied to flat terrain were 2.5359 m3/hour, 0.7128 m3/hour and 0.8186 m3/hour, respectively. But those on hilly terrain were 1.5540 m3/hour, 0.7374 m3/hour and 0.796 m3/hour, respectively. The average cost of full mechanical felling system applied to flat terrain was Rp 1,586.23/m3, while that of on hilly terrain was Rp 2,l 65.93/m3